EFFECT OF THERAPEUTIC DIABETIC NUTRITION ON GLYCEMIC KINETICS IN WOMEN WITH GESTATIONAL DIABETES MELLITUS - Степанов, Сергей Степанович; Шрайнер, Олег Александрович; Зырянова, Ирина Николаевна (Mother and Baby in Kuzbass, 2025)
The aim of the research – to evaluate the effect of the specialized dietary therapeutic diabetic mixture Nutriset D containing metabiotic complex and β-glucans on glycemic kinetics in women with gestational diabetes mellitus newly diagnosed in the third trimester of pregnancy.Materials and methods. The study involved 11 women with gestational diabetes mellitus who received a therapeutic and preventive diabetic mixture. Glucose was determined.Results. Patients had glycemia decreased to normal. Positive changes in bilirubin, potassium, sodium, absolute lymphocyte count and total protein were observed. Medical nutrition was well tolerated.Conclusion. The use in women with gestational diabetes mellitus of a therapeutic and prophylactic diabetic mixture, orally, in the amount of 400 ml 2 times a day for 7 days against the background of basic dietary therapy reduced glycemia.
Keywords: gestational diabetes mellitus; therapeutic diabetic nutrition